Challenges facing immediate tourism leveraging: evidence from the London 2012 Olympic Games. Issue 2 (4th March 2017) - Mhanna, Rami; Blake, Adam; Jones, Ian
ABSTRACT: Models of event leveraging identify strategies that organisers can use to increase the benefits that sport events bring to host destinations. Among these, leveraging tourism benefits during the event is a frequently cited strategy by which organisers can bring more money into a destination. To date, little work has been conducted on leveraging immediate tourism benefits from mega sport events. In addressing this issue, we reflect and present findings related to previously identified event leveraging theories that are determined by tourists' activities at a host destination. These are (a) enticing visitor spending and (b) lengthening visitor stay. The aim of this paper is to evaluate the use of such leveraging strategies during the London 2012 Olympic Games to increase event-related tourism. Results from 15 interviews with key stakeholders demonstrate that the effectiveness of these leveraging strategies can be limited by a number of challenges: (1) limited strategies to entice visitor spending, (2) limited interest in tourism attractions, (3) lack of location attractiveness, (4) the displacement effect and (5) the impact of the wider economic environment. Key challenges and opportunities are detailed, a discussion on the implications for event leveraging is provided and potential areas for future research are outlined.